2016
DOI: 10.4103/1119-3077.188713
|View full text |Cite
|
Sign up to set email alerts
|

Skull traction for cervical spinal injury in Enugu: A 5-year retrospective multicenter analysis of the clinical outcomes of patients treated with two common devices

Abstract: Crutch field tong traction may be associated with more complications when compared with Gardner-Wells traction. However, from our study, the final American Spinal Injury AIS outcome, as well as the overall mortality rates associated with the two traction techniques, did not vary significantly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 13 publications
(31 reference statements)
1
7
0
Order By: Relevance
“…The mean age and the male preponderance in this series are similar to other studies on CSI [4,12,20,22,23]. One of such studies found an average age of 42 years and males accounted for 76.8% of the patients [4].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The mean age and the male preponderance in this series are similar to other studies on CSI [4,12,20,22,23]. One of such studies found an average age of 42 years and males accounted for 76.8% of the patients [4].…”
Section: Discussionsupporting
confidence: 89%
“…In another study, the average age was 44 years and men were twice affected than women [24]. Other studies from Nigeria found average ages of 32.6 (±1.9 years) to 40.1 (±1.1 years) [20,22,23]. Young adult males are more likely to be involved in road traffic accidents (sustaining various injuries including CSI) because they are more mobile, adventurous, and more likely to be involved in sporting activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Chikuda's study, the mean age of patients was 60.8±18.7 [21]. In Eo Uche's study, the Mean±SD age of patients was 40.4±1.1 [22].…”
Section: Discussionmentioning
confidence: 88%
“…Demographic data, as well as the data regarding the type of patients' transportation to hospitals, pre-hospital care given to the patients (fixation, intubation, CPR in cases with cardiac arrest, interhospital transportation, Glasgow Comma Scale (GCS) both prior and subsequent to hospital admission, type of the neurological deficit, existence and type of the SCI, type of the non-surgical intervention, weight, duration and success rate of traction procedure, methylprednisolone administration, duration of stay of patients in Intensive Care Unit (ICU), and patients' outcome on discharge based on Glasgow Outcome Scale (GOS) were extracted from the registry system. The relative and absolute frequencies of each variable were assessed using the SPSS V. 22. A secondary analysis of the association between pre-hospital measures and the non-surgical interventions with patients' outcome was also carried out using discriminant analysis.…”
Section: Methods and Materials/ Patientsmentioning
confidence: 99%